pH-Responsive Allicin-Based Coatings With Antibacterial and Antifouling Effects in Marine Environments - Hao, Xiangping; Yan, Weilu; Sun, Ziqing; Yang, Jingzhi; Bai, Yun; Qian, Hongchang; Chowwanonthapunya, Thee; Zhang, Dawei (Frontiers in Materials, 2022)
In this work, we report the design of pH-controlled releasing behaviors polydopamine/tannic acid-allicin@chitosan (PDA/TA-ALL@CS) multilayer coatings to realize antibacterial and antifouling effects. The pH-responsive ALL@CS capsules were prepared by microemulsion method with about 262 nm to 452 nm diameter. The bacteriostasis of ALL@CS microcapsules against E. coli, S. aureus, and P. aeruginosa all exceed 94% as evaluated by the colony counting methods. Because of the protonation in acid environments and deprotonation in alkaline environments for the amino groups of CS, ALL as biocides can be released from the nanocapsules and exert outstanding antibacterial properties. Confirmed by the plate colony counts, the ALL@CS capsules possessed an outstanding antibacterial effect for E.coli in acid solutions but were less effective in alkaline solutions. The PDA/TA-ALL@CS-7 coatings showed durable pH-responsive antibacterial activities with an efficiency of ~87% after immersion in pH 8 solutions for 7 days. The PDA/TA-ALL@CS coating with controlled release performance and antibacterial properties may provide a new solution for developing antifouling coatings applications in the marine environment.